2023
DOI: 10.15644/asc57/1/3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hospital-Based Dental Procedures Under General Anesthesia in Uncooperative Patients: a Retrospective Study

Abstract: Background General anesthesia is a well-documented therapeutic option for the provision of dental treatment, particularly in patients with special healthcare needs and uncooperative pediatric patients. Objectives This retrospective study aimed to analyze the characteristics of dental general anesthesia (DGA) procedures for uncooperative patients of all ages in a tertiary healthcare facility, Clinical Hospital Dubrava, in Zagreb, Croatia. Material and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A lack of adequate dental treatment leads to more missing teeth and fewer filled and sound surfaces over time [ 68 ]. Furthermore, children who undergo painful surgery and are treated under dental general anaesthesia at a young age are more likely to develop dental fear than those who have had positive or neutral dental experiences prior to their first painful surgery [ 69 , 70 ]. In a study conducted by Vanhee et al [ 71 ], it was observed that DFA among paediatric patients exhibited clear bimodal distributions, particularly in response to factors like the sight of a syringe, the sight and taste of blood, and tooth extraction.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of adequate dental treatment leads to more missing teeth and fewer filled and sound surfaces over time [ 68 ]. Furthermore, children who undergo painful surgery and are treated under dental general anaesthesia at a young age are more likely to develop dental fear than those who have had positive or neutral dental experiences prior to their first painful surgery [ 69 , 70 ]. In a study conducted by Vanhee et al [ 71 ], it was observed that DFA among paediatric patients exhibited clear bimodal distributions, particularly in response to factors like the sight of a syringe, the sight and taste of blood, and tooth extraction.…”
Section: Discussionmentioning
confidence: 99%